Functional Properties of Four Cucurbits Found in Nigeria - Franca, Okoye Ngozi (Pakistan Journal of Nutrition, 2012)
The functional properties of four cucurbits grown in Nigeria namely, snake tomato Trichosanthes cucumerina, cucumber Cucumis sativus, pumpkins Cucurbita pepo and Cucurbita moschata were investigated. The effects of pH and NaCl concentrations on some of these functional properties were also determined. The highest water absorption capacity was observed in Cucurbita pepo (4.80 g/g) and Trichosanthes cucumerina as lowest (1.80 g/g). Similarly, Cucrubita pepo had the highest oil absorption capacity (1.10 g/g) and Trichosanthes cucumerina had the least (0.17 g/g). The samples had good gelation capacity. Cucurbita pepo gave the highest gelation at (6.67%) and Trichosanthes cucumerina gave the least at (12.67%). Cucumis sativus showed the highest emulsification capacity (6.5 g/g) and Trichosanthes cucumerina, the lowest at (4.2 g/g). NaCl and pH influenced the emulsification capacity. The samples did not show any remarkable percentage volume increase in the foaming capacity and pH and NaCl did not influence the foaming capacity. The sample showed that they could be utilized in the formulation of new foods.